Interest in and Awareness of French President Emmanuel Macron’s “Make our Planet Great Again” Initiative - Joshua S. Dadural; Leah R. Reznikov (Social Sciences, 2018)
President Donald Trump’s withdrawal from the Paris Agreement served as an impetus for the French President to enact “Make our Planet Great Again”, an initiative aimed at attracting international scientists to study climate change. In the current study, we evaluated the extent of interest and awareness towards this initiative. Our goal was to determine factors that impacted awareness and interest, with the hypothesis that political views and beliefs towards climate change would be strong influencers. We also predicted that there would be a greater number of scientists among the aware and interested participants. To test these hypotheses, we distributed anonymous online surveys during October–November 2017 to multiple academic departments within the University of Florida, a land grant institution with top ranking programs in environmental sciences, agriculture, biodiversity conservation, and horticulture. We recruited 185 participants. Approximately 45% of the participants were aware of French President Macron’s initiative; of those aware, 51.8% expressed interest. We found a moderate influence of political party on awareness and interest. Nearly all of the participants that were aware and interested in the initiative agreed that climate change was a real event. Slightly lower agreement was reported by the unaware and uninterested. Surprisingly, there were fewer scientists among the aware and interested participants compared to those that were unaware and uninterested participants. These findings highlight that both political party and belief towards climate changed influenced interest and awareness in President Emmanuel Macron’s initiative. Thus, employing strategies that engage all political parties, as well as educating individuals on climate change, might result in more effective future global initiatives.